Assessments by principals, teachers, and parents on values education in Estonian kindergartens. Issue 4 (2nd October 2018) - Ülavere, Pärje; Veisson, Marika
Abstract: The objective of this study was to analyse assessments made by principals, teachers and parents regarding the performance of values education in Estonian kindergartens. Six fields of activity were investigated: formulating and explaining values, promoting values, having a systematic approach towards values education, kindergarten culture, collaboration, and development activities related to values education. The authors also sought to identify the main values in preschool childcare institutions/kindergartens. Altogether, 978 respondents across Estonia returned the questionnaire. Principals, teachers and parents consider values education in kindergartens to be very important. Parent assessments of childcare institution activities related to values education are mostly lower than those given by teachers and principals, while parents assess collaboration with kindergartens at a higher level and emphasise their own part in the values education of a childcare institution. Discussions with teachers and parents play a significant role in kindergartens. It was mostly collaboration that was named as the core value for a kindergarten, followed by safety, caring, openness, child-orientation, health, trust, friendliness, traditions, professionalism, honesty and tolerance.